Semantic relations in the argot language of youth - Massumeh Poloie; Mohammad reza Ahmadkhani (زبان پژوهی, 2019)
The Argot language is one of the standard varieties of language that is formed among young people or a group of delinquents. Each social group has its own terms and expressions that must be learned in order to enter that group. Argot language is not separate from the language. Rather, it is one of its various varieties. This language represents a heterogeneous society, with each group having an impact on language. One can argue beyond this, claiming that the difference between each Argot language and the language commonly depends on the group attribute that uses this Argot language. The more different these groups are, the more they use different language forms to establish and maintain a relationship with the linguistic community. Young people form a large part of the active population of our community and the tendency towards peers and differences with adults are important features of this group. They have a particular language system that consists of the norms, values, behaviors and the core of their subculture. It is a secret code and a special communication symbol that transmits messages and creates certain rules and behaviors. Therefore, young people have their own subculture and use special vocabulary. The use of these vocabulary by young people and their influence on the youth subculture has created a certain verbal and non-verbal communication among young people that requires a scientific review. Groups and circles of friends, SMS, social networking messages, television movies, virtual social media, print media such as fictional characters, borrowing from other languages, and other forms of creativity are the means for dissemination of these words. The purpose of this paper is to identify semantic relations in the secret language within the framework of the theory of constructivism. Constructive semantics is one of the most important methods of achieving analysis using structuralism theory. In this view, the network language is one of the systematic relationships. Structural meanings refer to what the equivalent of a semantic unit is and how they are connected. The constructive semantic label is usually limited to lexical semantics. One of the most fundamental and general principles of constructivist linguistics is that languages, systems, and sub-systems or their constituent levels –grammatical, lexical, and phoneme levels– are interdependent. An important aspect of lexical semantics is how semantic relations of vocabulary are with each other; in particular, the discovery of the four classes of semantic relations, opposition, hyponymy, synonymy, and member-collection is important. Semantic Relationship is the relationship between  lexical categories with other vocabulary, which confronts the speaker with the choice of different lexical categories. This term has different types. In other words, the meaning of the semantic relation is that the language has a semantic structure and the words are related in groups. Of course, these groups are formed on the basis of the semantic relations between the words. According to the tradition of studying meaning, these relations are in the semantic system of language between concepts that at first glance may seem independent, but have a close connection with each other, which is sometimes impossible to distinguish them from one another. Conceptual relationships have two types. Some of them are substitutions, and the others are synthetic, or, according to the famous statement, according to the Saussure’s attitude, is a function of substitution and conjunction. The substitution relationships between concepts arise among members of a grammatical category and with their replacement. This category of conceptual relationships, typically and not necessarily, consists of words from various grammatical categories that together create well-formedness. In order to achieve the purpose of the article, we first discuss the categories of semantic, synonymy, polysemy, opposition, hyponymy, meronymy, collocation, portion-mass, member-collection, homophony and homography. After processing and identifying these relationships in the Argot language vocabulary derived from an interview of the 15-30 year old young people in Tehran subway, as well as the Persian Dictionary of Argot of Samai’s work, the frequency of each semantic relationship was determined. The sample size is 1507 words; it has been extracted by two methods of documenting the Persian Dictionary of Argot and a researcher-made interview with a Snowball Sampling method. After collecting and deletion, the words were classified according to their nature and meaning in fourteen semantic areas. These classes include tools and objects, automobiles, moods, ethics and behavior, secret communication, the condition of organs, numbers, organs, eating and drinking, people, actions, opiates, clothing and places. The information of each word includes the semantic domain, the concept, the lexical entry and the Encyclopedia meaning. In addition to identifying semantic domains, the concept of each lexical category was also identified. Because the creators of the Argot language vocabulary use or create these words in an attempt to keep secrets hidden within a group of their inherent knowledge, the words reference may be different from these concepts. Then, the semantic relations of lexical data in each area were determined by qualitative content analysis method. The question of this research is if semantic relations exist in the secret language and what the relationship between the highest and lowest frequencies of semantic relations is. The results of the derivation of semantic analysis show that the highest and lowest lexical frequencies belong to the domains of people and clothing, respectively. Also, synonymy with the frequency of 63.05% has the highest semantic and homography with the frequency of 0.11% has the least semantic relation. The high frequency of synonymy relation in the vocabulary of this language represents the main reason for the use of Argot language; that is, to hide the meaning of these words. If these meanings are revealed to others, new terms replaces the previous words.